Karakteristik Mortar Komposit Dengan Penambahan Arang Aktif - Sadir, Muhammad; Mirawati, Baiq; Wangiyana, I Gde Adi Suryawan; Hendriko, Albert; Irama, Ade; Hidayah, Zoya Saharani; Hafiz, Yusron (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
The addition of activated charcoal to the cement matrix can increase the density and durability of the mortar. The purpose of this study was to analyze the effect of activated charcoal on the characteristics of composite mortar including compressive strength, density, and water absorption. Making mortar composite with the composition of activated charcoal to the weight of cement (1%, 2%, 3%, 4%, and 5%), the ratio of cement and sand is 1: 3. The composition will be tested and analyzed for its effect on the compressive strength, density, and water absorption of mortar composite. The results showed that the addition of activated charcoal did not have a significant effect on the characteristics of mortar composite, except for the setting density. The addition of activated charcoal by 5% showed an optimal composition with a compressive strength value of 11.67 MPa, a setting density of 2092.91 kg / m3, an oven-dry density of 1853.93 kg / m3, and a water absorption of 15.20%